A Kerma Ancien cemetery in the Northern Dongola reach excavations at site H29 - Welsby, Derek A. 1956- (SARS, 2018)
This volume is the final report on the excavations of a Kerma Ancien cemetery discovered by the Sudan Archaeological Research Society during its Northern Dongola Reach Survey conducted between 1993 and 1997. It is one of the very few cemeteries of this date to have been fully excavated and provides interesting data on funerary culture as practised in a rural environment, to be compared with the extensive information available from investigations of the cemetery associated with the metropolis of Kerma 100km to the north. It includes a range of specialist reports on all categories of artefacts recovered as well as on the physical anthropology, archaeobotany and archaeozoology
Previously issued in print: 2018. - Includes bibliographical references
Keywords: Excavations (Archaeology) / Sudan / Karmah; Cemeteries / Nubia; Funeral rites and ceremonies / Nubia; Ausgrabung; Friedhof; Antike; Karmah (Sudan) / Antiquities; Sudan; Nubien; Dongola; Aufsatzsammlung